Test of the Effectiveness of Anti-Dyslipedemia Extract Ethanol Mangosteen Peel (Garcinia Mangostana L.) in Male Mice Fed a High-Fat Diet - Zhang Yu; Florenly; Liena; Fioni (Britain International of Exact Sciences (BIoEx) Journal, 2022)
Dyslipidemia is a major risk factor for atheroscler heart disease, stroke, and is often defined as abnormalities or disruption of lipid metabolism. Garcinia mangostana L. is famous for its anti-inflammatory properties and is used in the treatment of skin infections and wounds. The main phytochemicals present in this species are anisoprenylated xanthone, many reports of biological effects, such as antioxidant, pro-apoptosis, anti-proliferative, anti-nosiseptif, anti-inflammatory, neuroprotective, hypoglycemic, and anti-obesity. This study aims to find out the effectiveness of mangosteen peel ethanol extract as an anti-dyslipidemia in male wistar rats given a high-fat diet. This type of research is experimental with a Pre-test approach and Post-test group only control design. The samples used were mangosteen peel ethanol extract and male wistar rats, with the size of the sample calculated with Federer's formula. Analyze data with the One-Way Anova Test if the data is normally distributed with advanced tests in the form of Post Hoc Tukey HSD tests to see real differences between treatments. The results of the total cholesterol study in the entire treatment group of mice showed a significant difference in P values < 0.05. Triglyceride levels in the entire treatment group also showed significant differences, this can be seen from the value of P < 0.05 (Value P = 0.029). LDL levels also showed significant differences across the treatment group, which can be seen from the P value of < 0.05. HDL levels make a significant difference in the value of P < 0.05 (Value P = 0.029). SGOT and SGPT levels in the entire group of rat treatment showed significant differences, this was seen from the value of P < 0.05. The conclusion that mangosteen peel ethanol extract significantly lowered total cholesterol, triglyceride levels, LDL levels, SGOT levels compared to the control group. Mangosteen peel ethanol extract can significantly increase HDL levels compared to the control group.